Manajemen Strategik dalam Meningkatkan Mutu Pelayanan Kepegawaian pada Dinas Pendidikan Kota Solok - Riandani, Ade; Syafwandi, S; Pratama, Eri; Andika, Afri (SAFE-Network, 2024)
Strategic Management plays an important role in improving the quality of personnel services at the Solok City Education Office. The aim of this research is to explore information regarding the implementation of strategic management, especially in the context of personnel services, as well as its impact on the quality of personnel services at the Solok City Education Office. This research uses a qualitative method with a case study approach, and data analysis is carried out using the Miles and Huberman Interactive analysis model. Research findings show that the Solok City Education Office implements strategic management in personnel services by referring to the Provincial RPJP and Solok City RPJMD. This process involves the stages of strategic planning, strategy implementation, and strategy evaluation. The quality of personnel services at the Solok City Education Office has experienced a significant increase after the implementation of strategic management, which can be proven by the fulfillment of the five main dimensions of service quality.